Pay Survivors for Our Lived Experiences - MC, Tamara (Anti-Trafficking Review, 2024)
This short paper argues that to address the exploitation of survivors’ labour in anti-trafficking work, it is essential to allocate funds towards compensating survivors for their contributions. This funding should prioritise paying survivors for sharing their expertise and lived experiences, which are invaluable for effective anti-trafficking efforts. Establishing a standard pay rate, commensurate with other expert consultants, would validate survivors’ roles and contributions, promoting sustainable engagement and preventing further exploitation within the anti-trafficking movement.